HUBUNGAN INDEKS MASA TUBUH (IMT) DENGAN KEJADIAN HEMOROID DI BAGIAN BEDAH RSI SITI RAHMAH - Ahmad Dzaki; Melya Susanti; Zukhri Zainun (Yayasan Nusantara Hasana Berdikari, 2025)
Hemorrhoids are localized dilations of vascular structures caused by the migration or pathological hypertrophy of the pads in the submucosal layer of the lower rectum. In the United States, hemorrhoids are the fourth most common outpatient gastrointestinal diagnosis, accounting for 3.3 million outpatient visits annually. According to Basic Health Research (Riskesdas) data in 2018, approximately 12.5 million Indonesians suffer from hemorrhoidal disease. Factors commonly associated with an increased risk of hemorrhoids include constipation, a low-fiber diet, high body mass index (BMI), pregnancy, and a sedentary lifestyle. This study aims to determine the relationship between body mass index (BMI) and the occurrence of hemorrhoids in the surgical department of RSI Siti Rahmah Padang during the period January 2022 to August 2023. This research employed an observational analytic method with a cross-sectional design. The study sample consisted of patients from the surgical clinic of RSI Siti Rahmah Padang within the specified period who were diagnosed with hemorrhoids, selected using a simple random sampling technique. Data were obtained from the medical records of 166 patients who met the inclusion criteria and were analyzed using the chi-square test. The results showed that the highest incidence of hemorrhoids occurred in adults, with 23 cases (51.1%). Based on gender distribution, females accounted for 27 cases (60%). Regarding BMI, the majority of patients were classified as overweight, with 22 individuals (48.9%) suffering from hemorrhoids. Data analysis demonstrated a significant relationship between BMI and the incidence of hemorrhoids (p = 0.000).